2020
DOI: 10.1109/jphot.2020.3026973
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Image Segmentation Algorithm Based on Saliency Map and Neutrosophic Set Theory

Abstract: Due to more or less deviations in the imaging system, there will be noise in the image, which makes the image segmentation inaccurate. To divide a natural image into a more accurate binary image, the target and background of the image are effectively separated to achieve a more effective segmentation result. Therefore, this paper proposes an image segmentation algorithm combining a saliency map and neutrosophic set (NS) theory. First, to overcome the problem of weak edges in the image, we highlight the details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, sports learning researchers mainly analyze the ideal feedback timing, feedback form, and feedback frequency in feedback training to provide an ideal operation scheme for the digitization of sports training [16]. is algorithm is developed according to the concept of change detection, which is different from the other change detection methods [17]. e video segmentation algorithm does not use the difference between the two consecutive images to judge motion.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, sports learning researchers mainly analyze the ideal feedback timing, feedback form, and feedback frequency in feedback training to provide an ideal operation scheme for the digitization of sports training [16]. is algorithm is developed according to the concept of change detection, which is different from the other change detection methods [17]. e video segmentation algorithm does not use the difference between the two consecutive images to judge motion.…”
Section: Related Workmentioning
confidence: 99%
“…Yuan [2] proposed a new image segmentation method based on INS, and the experimental results showed that it achieved higher PSNR values and performed better than the k-means clustering algorithm. Song [3] proposed a fast image segmentation method that combines a saliency map with NS (SMNS) to achieve higher accuracy. The SMNS method can effectively solve the issues of under-segmentation and over-segmentation, and performs well in the presence of salt and pepper noise, Gaussian white noise, and mixed noise.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the perception of the fuzzy-based approaches is generalized by the neutrosophic set. It includes the fuzzy set and intuitionistic fuzzy set [ 29 ]. In the NS domain, Guo and Cheng introduced fuzzy c-means clustering, and the indeterminacy of the image is calculated by the entropy.…”
Section: Introductionmentioning
confidence: 99%